Evaluation of apples coated with biodegradable polymers added extract from the cask stem bark (Research, Society and Development, 2020)
The production of fruits and vegetables generates losses during the production and storage process, reaching a loss of 20% to 40% in their production, this situation can be favored by numerous factors, such as the absence or deficiency of methods conservation. The aim of this study was to evaluate the influence of cashew stem extracts on edible coatings. Four treatments were evaluated, being these: T0: Fruit without coating (control); T1: Fruit coated with coating without extract; T2: Coating added with 3% extract; T3: Film added with 6% extract. The treatments were evaluated at room temperature (30 ° C) and under refrigeration (7 ° C). All treatments were submitted to the analysis of Firmness (N) and Loss of mass (%) in the period of 0, 3, 6, 9, 12 and 15 days. The coating with the addition of 3% of the cashew nut obtained the best results in reducing the loss of mass of the fruits during their storage period. Being able to observe at the end of the experiment the efficiency of the casing coating of the cashew stem, which makes its application a possible suggestion in the food industry for the conservation of fruits submitted or not under refrigeration.